A TYPOLOGY OF RURAL AREAS IN SERBIA - Bogdanov, Natalija; Meredith, David; Efstratoglou, Sophia (Economic Annals, 2008)
The goal of this paper is to present a method to establish the typology of rural areas in Serbia. Initially the OECD rurality criterion was applied to define the rural areas in Serbia. Subsequently, relevant indicators were selected (demographic, geographic, economic, employment-related, human capital, agricultural, tourism and infrastructure) and used to define and distinguish relatively homogeneous rural regions, based on correlation analysis, factor analysis (VARIMAX method) and cluster analysis. Cluster analysis revealed six regions of different sizes and characteristics. Practical considerations reduced this to four types, resulting in a robust scheme which accurately reflects the heterogeneous nature of rural Serbia.